2065. Whole Genome Sequencing for Antimicrobial Resistance Prediction in MRSA and VRE: A Real-world Application. (26th November 2018) - Babiker, Ahmed; Mustapha, Mustapha M; Doi, Yohei; Harrison, Lee H
Abstract: Background: The antimicrobial resistance (AMR) crisis represents a serious threat to public health and the healthcare economy. The impact of increasing AMR has resulted in concentrated efforts to increased rapid molecular diagnostics of AMRs. In combination with publicly available web-based AMR databases, whole-genome sequencing (WGS) offers the capacity for detection of antibiotic resistance genes with low turnaround times and is becoming increasingly affordable. Here we sought to examine concordance between WGS-based resistance prediction and phenotypic susceptibility testing results for prospectively collected VRE and MRSA clinical isolates using publicly-available tools. Methods: MRSA and VRE isolates were prospectively collected and underwent WGS at the University of Pittsburgh Medical Center (UPMC) between December 2016 and December 2017. Antibiotic-resistant gene content was assessed by uploading assembled contigs to ResFinder, NCBI betalactamase and CARD using a BLASTn.search. Routine susceptibility was performed by Microscan™. Concordance between genotypic and phenotypic as well as sensitivity, specificity, positive and negative predictive values methods were calculated for each antibiotic/organism combination, using the phenotypic results as the gold standard. In case of discordance between the methods, repeat susceptibility using disc diffusion results was performed and was then considered to be the gold standard method. Results: Phenotypic susceptibility testing and WGS results were available for 109 and 105 unique MRSA and VRE isolates, respectively. Out of total of 1, 058 isolate/antibiotic combinations overall concordance of WGS-web-based prediction with phenotypic susceptibility methods was 99.1% with a sensitivity, specificity, PPV, NPV of 98, 99.6, 99.5, and 98.3%, respectively. Specific concordance for MRSA isolates was 98.8%. with a sensitivity, specificity, PPV and NPV of 97.6, 99.8, 99.7, and 98.5% (Table 1), while concordance for VRE isolates was 99.3%, with a sensitivity, specificity, PPV and NPV of 98.6, 98.1, 99.1, and 97.2% (Table 2). Conclusion: WGS is a reliable predicator of phenotypic resistance for both MRSA and VRE. Disclosures: All authors: No reported disclosures.